«Prospectus» from L’Artiste, by Théophile Gautier. Preliminary note and translated text (El Hilo de la Fabula, 2024)
The «Prospectus» that Théophile Gautier wrote for the renewed proposal presentation of the newspaper The Artist –of which he had been, since 1856, the editor-in-chief chosen by the editors Édouard Houssaye and Xavier Aubryet–, is an important text about the debates about the autonomy of art or its subordination to the political ideologies of the time. Despite his importance, Gautier has fallen into a certain disrepute for the community of researchers, at least in the Spanish language, to such an extent that not only are studies on his works scarce, but also, to this day, this text has not been translated and is only mentioned in some studies on aesthetic ideas for his famous phrase «we believe in the autonomy of art (...)».